COVID-19 as a Potential Target for Cryobiology and Cryomedicine - Goltsev, Anatoliy; Fuller, Barry; Bondarovich, Mykola; Babenko, Natalya; Gaevska, Yulia; Buriak, Iryna; Dubrava, Tatyana; Yampolska, Kateryna; Lutsenko, Olena; Ostankov, Maksim (Problems of Cryobiology and Cryomedicine, 2020)
The review presents data on immune pathogenesis of COVID-19 and approaches to its prevention and treatment. The low effectiveness of antiviral drugs is caused by the ability of SARS-CoV2 virus to change its own structure and functions. Existing treatment strategies of COVID-19 are focused on applying the direct antiviral therapies, modulation of innate immune response, "cytokine storm" suppression and use of convalescent plasma. Deregulated interaction between innate and adaptive immune systems determines the start of autoimmune process in the virus carrier body, that requires the use of alternative ways to prevent such diseases using cryobiological technologies. The results of studying the immune biological activity of cryopreserved human cord blood leukoconcentrate (cHCBL) and its components by preventive intranasal administration have been presented. The effectiveness of cHCBL is related to the possible reprogramming of the genes responsible for the implementation of the body's immune responses and induction of the "trained" immunity. Such a modification of the immune system state can be the most promising in protecting the body against viruses, in particular COVID-19. Probl Cryobiol Cryomed 2020; 30(2): 107–131